The Use Of Superheated Steam Treatments On Rice Flour To Enhance The Quality Characteristics Of Laksa Noodles - PPTI, Pusat Pengajian Teknologi Industri (Universiti Sains Malaysia, 2021)
Laksa noodles, also known as rice noodles, are the most popular rice products in Southeast Asia. The products made from rice, are usually prone to harden; later, their texture and taste will lose over time because of the recrystallization properties of starch’s amylose and amylopectin. This study was aimed to evaluate the effects of using superheated steam on the rice flour (SHSRF) on the physical properties, cooking, eating, and sensory quality of laksa noodles produced. Two conditions of SHSRF were selected; a) low temperature at 150oC (RF150) and b) high temperature at 250oC (RF250). The comparisons between rice noodles were made from these two conditions vs. fresh noodles (FN). Both treatments significantly (P<0.05) affected the physical properties, cooking, and eating quality of rice noodles. Rice noodles prepare from both treatments were higher in yellowness and had stronger tensile strength than those of FN. The treatments also caused a reduction in cooking time, and improvement in cooking quality compared to FN. Hardness of rice noodles was in the order; RF250>RF150>FN indicating an improved eating quality of rice noodles prepared from SHSRF. In summary, superheated steam may be used for physical modification to change rice flour properties to enhance the cooking and eating quality of rice noodles.